2016
DOI: 10.1016/j.jinf.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia due to carbapenem-resistant Enterobacteriaceae in neutropenic patients with hematologic malignancies

Abstract: Objectives To determine the prevalence, risk factors, treatments, and outcomes of bloodstream infections (BSIs) due to carbapenem-resistant Enterobacteriaceae (CRE) in adult neutropenic patients with hematologic malignancies. Methods We reviewed all BSIs between 2008–2012 in this population at two New York City oncology centers. A case-control study was conducted to identify CRE BSI risk factors, using three controls of non-CRE BSIs per case. Results CRE caused 43 (2.2%) of 1,992 BSIs overall and 4.7% of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 27 publications
10
113
4
2
Order By: Relevance
“…We demonstrated higher mortality rates in infections caused by resistant ba similar to other studies [8,12]. Analysis of mortality risk factors is beyond t of this manuscript.…”
Section: Outcomesupporting
confidence: 86%
See 1 more Smart Citation
“…We demonstrated higher mortality rates in infections caused by resistant ba similar to other studies [8,12]. Analysis of mortality risk factors is beyond t of this manuscript.…”
Section: Outcomesupporting
confidence: 86%
“…Onl handful describe risk factors for carbapenem-resistant infections in popula involving but not limited to transplant patients, mainly for K. pneumoniae. D from other studies, we found that breakthrough on noncarbapenems does n predispose to carbapenem resistance in allo-HSCT patients [8,14]. Noncarb may be explained by increased resistance rates over time [5].…”
Section: Outcomementioning
confidence: 62%
“…Interestingly, immunosuppression and longer time to active antibiotic therapy were associated with decreased mortality. Two prior studies conducted at our institution evaluated immunocompromised patients with bacteremia due to CRE and found that death often occurred within 3 to 4 days of BSI onset (23,24). This early mortality may have resulted in many of the more severely ill immunocompromised patients being excluded because they did not receive 48 h of polymyxin B.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Biofilm facilitates MRSA survival and multiplication, prolonging the organism's exposure to antibiotics as well as promoting the transfer of antibiotic resistance genes among strains. 49 53 Multiple antibiotics, steroids and prior CRE colonization were determined to be risk factors for CRE BSI, and delay in receipt of CRE-active therapy was associated with worse outcomes. First described in India, New Delhi metallo-β-lactamase-1 (NDM-1)-producing CRE have since spread globally.…”
Section: Emerging Resistance In Bloodstream Infection Pathogens In Thmentioning
confidence: 99%